Red, white and sparking : an analysis of wine consumption patterns in Singapore and proposal for the setting up of a wine shop - Ee, Min Hoon (2008)
Wine consumption in Asia started taking off in 1993. Wine consumption in Singapore doubled between 1990 and 1995 to 45,000 hectolitres and dollar spending increased by 115 percent from $38 million to $81 million. The objective of this study is to determine the feasibility of setting up a wine shop in Singapore and develop a business plan for it.